PENGARUH KANDUNGAN LEMPUNG DAN KADAR AIR TERHADAP COHESI DAN PHI TANAH LANAU BERLEMPUNG - Endaryanta, Endaryanta (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT In this year, landslide disaster such as embankment slide, bank slide, or buried of soil (trash) often occurs. All of them begin with a simple problem, that is infiltration of rain water (or other) into soil causing the decrease of shear strength, finally passed the limit of landslide safety factor F, so landslide occurs. The research tries to know the behavior of clayey-mud soil with several ratio of clay content and several water content ratio to find out how much clay content and water content (w) may induce soil collapse. This experiment research was conducted in the soil laboratory UNY using clayey-mud soil from Klaten which has been conditioned in several clay content (00/0-400/0) and water content w (20%-30%) and then direct shear tests were applied. The product of this experiment were: cohesion (c), internal soil shear angle, phi (<p), and safety factor of landslide (F). This research has resulted: (1) For pure mud soil, until 25% water content, would decrease of cohesion (interlocking), but >25% water content,interlocking (cohesion) would constant. The maximum cohesion (interlocking)(0.09 kg/cm2) reaches at 20% of water content (2) For pure mud soil, increasing of water content until 30% would increase of <p and F. The maximum <p value (41.8°) occur at 30% water content (at 0% clay content); (3) For clayey-mud soil, increasing of water content causes increasing or constant of cohesion. The cohesion would increase if 10%-20% clay content. The c value until 0.0665 kg/cm2 at 30% water content (at 100/0 clay content); and (4) For clayey-mud soil, increasing of water content (until 25%) would increase of <p and F. The <p value could until 40.9° at w=25% (at 10% clay content). If w>25%, the value of <p and F would decrease. The <p value until 7.7° at w=300/0 (at 40% clay content). Keywords: mud. clay, soil, water content, cohesion, landslide.